Consumer Behaviour towards QR Code Payments in Malaysia: The Case of Touch ’n Go e-Wallet - Kishan Singh Rathore; Yee Huei Lok; Ranjith PV; Gungun Chauhan; Chia Xin Yi; Chin Shao Xuan; Chiam Qian Hei; Chin Qian Hui; Anshika Agarwal; Abhijeet Krishnat Shinge; Daisy Mui Hung Kee (Asia Pacific Journal of Management and Education (APJME), 2026)
In recent years, Malaysia has rapidly transitioned from cashless to contactless transactions, emerging as the second-highest user of QR code payments globally. This study is about figuring out what makes people want to use QR code payments in Malaysia. We are looking at people who use Touch ’n Go E-Wallet. Even though we have lots of payment options many people are still not sure, about using QR code payments. We want to understand why this is happening. Hence, we are using Technology Acceptance Model to look at five things which are how easy QR code payments are to use, how useful they are, if they are safe and trustworthy if they are good value and if they work well with other things. Data was collected from 200 respondents conducted through online survey. The results of the regression analysis show that consumer intention is strongly influenced by perceived value, convenience of use, and usefulness, while trust and security are critical for continued usage. These results provide valuable insights for fintech developers and policy makers.